Fusões, aquisições e internacionalização do setor bancário na América Latina (1990 - 2002) - Andreatta, Jane Cristina (2004)
A series of mergers and acquisitions (M&A) is reported daily by the press. In fact, it is an intense movement, verified not only in developed countries, but also in those called developing countries. The sector / / financial is no exception. This is one of the sectors that received the most investments / foreigners in Latin America throughout the 1990s. In its origin, there are several; factors associated with the “globalization” of production and finance, a phenomenon stimulated by the rapid and growing international liquidity, associated with the creation and dissemination of new financial instruments, with emphasis on the expansion of technical progress and services and the i new technologies of transmission of information. With regard to State reform, 1 the general deregulation of activities, observed on a global scale, and the privatization processes in Europe and, more recently, in Latin America, stand out. Wealth restructuring in the financial sector is not new. This began in the United States in the 1960s. Its European dimension would have started in the 19th century and, more recently, spread to the rest of the continent. Emerging countries already formed a more recent front in this regard in the 1990s, with the exception of some Southeast Asian countries, which underwent processes of this type in the years 1980. The objective of these restructuring processes, in general, is, according to BONELLI (2000), to make the companies and conglomerates in which they participate more efficient and competitive due to changes in the forms and sectors of capital application. In this line of argument, two main factors were pointed out to explain the M&A wave in the 1990s: the first was the movement carried out by conglomerates with businesses in different sectors that, for strategic reasons, try to get rid of accessory businesses in order to concentrate whether in the main, or core businesses. The second would be the need to obtain synergies through the merger, acquisition or joint venlure, with projects located in its main sector. In both cases, M&A can take place in cross-border operations, as occurred in great intensity in the 1990s, in Latin America. Large international corporations sought, in Latin America, a way to consolidate their active internationalization process, seeking the increase in their mcirket-share and competitiveness, entry into an expanding market in which they could exploit organizational and technological resources and capabilities, in addition to diversifying risks according to profitability. In this way, the determinants and the results of the processes of '■ -jf M&A and of the strategies of patrimonial internationalization in the banking sector will be analyzed, in four countries of Latin America - Argentina, Brazil, Chile and Mexico -, and their impacts on the degree of concentration. It is important to highlight that, in the database prepared for this work, the financial sector is comprised of banks, insurance companies and brokers. Therefore, like banks, they are the ones with the highest number of transactions, and these are also the most relevant, since the work will be concentrated mainly on mergers and acquisitions and internationalization of: banks to the countries mentioned above. In this perspective, the work is divided into three chapters. Chapter I has two sections: the first aims to define the terms referring to the theme, that is, to define what is merger and acquisition and what is internationalization. Thus, some authors who have studied the topic are briefly shown. In the second section, the objective is to show, in detail, how the database was refined so that the elaboration of the work could be viable. Chapter II aims to analyze the favorable conditions for bank mergers and acquisitions in Latin America, seeking to describe two primary factors: external factors, which correspond to the tendency of large international banks to expand to other markets, an attitude that was driven by changes in the global macroeconomic environment, technological and financial innovations and the liberalization and deregulation of the developed countries' financial markets, stimulating a dispute between the big banks tending to secure new market shares. The second factor would be internal, that is, what changes have occurred in Latin America to make the coming of these foreign banks to the region viable, thus, the restructuring processes of the financial systems of Argentina, Brazil, Chile were described and Mexico addressing the characteristics and structural problems of each of them. Chapter III shows, concretely, these changes mentioned above, based on the Thomson Financial Securiíies Data base, and aims to discuss the main conclusions drawn from the analysis of this database. Finally, there are the final considerations, which resume the main points raised in the study and its conclusions.